A Novel Approach to Evaluate the Benefits of Casing Treatment in Axial Compressors - Guillaume Legras; Isabelle Trébinjac; Nicolas Gourdain; Xavier Ottavy; Lionel Castillon (International Journal of Rotating Machinery)
Passive control devices based on casing treatments have already shown their capability to improve the flow stability in axial compressors. However, their optimization remains complex due to a partial understanding of the related physical mechanisms. In order to quantitatively assess the interaction between slots and the blade tip flow, the present paper develops a novel analysis methodology based on a control-volume approach located in the rotor tip region. This methodology may be used for analyzing the casing treatment based on both axi- and non-axisymmetric slots design. The second issue of the paper focuses on the application of the current approach to better understand the effects of axi- and non-axisymmetric grooves in three different axial compressors which differ by the flow regime (subsonic/transonic) and the smooth casing shape (cylindrical/concave). Numerical simulations are performed, and results of the current approach with and without casing treatments are compared.